Stability of ionic-covalently cross-linked PBI-blended membranes for SO2 electrolysis at elevated temperatures. (24th January 2020) - Peach, Retha; Krieg, Henning M.; Krüger, Andries J.; Bessarabov, Dmitri; Kerres, Jochen
Abstract: In this study, the effect of component composition on the chemical stability of the developed ionic-covalently cross-linked PBI-blended membrane concept from earlier studies for application in SO2 electrolysis at elevated temperatures (>100 °C) is further investigated. Three different acid-base ratios were studied by blending a partially fluorinated sulfonated arylene main-chain polymer (SFS) with polybenzimidazole (F6 PBI) and a partially or non-fluorinated bromo-methylated polymer (BrPAE). In addition two different alkylated imidazoles (EMIm and TMIm) were included as quaternization agents. Accordingly, twelve different PBI-blended membranes were produced in this study. The suitability of these membranes for SO2 electrolysis at elevated temperatures was determined in terms of i) the H2 SO4 stability (80 wt% H2 SO4 at 100 °C for 120 h), (ii) the oxidative stability (Fenton's test, FT) and (iii) the organic solvent stability (extraction in N, N-Dimethylacetamide). Membranes were characterized in terms of the percentage weight, the ion exchange capacity (IEC) and the thermal stability (TGA-FTIR) changes, before and after the various treatments. Although all blended membrane types were sufficiently stable during H2 SO4 treatment, proton conductivity measurements indicated that the blends containing only partially fluorinated blend components displayed superior stability (better compatibility) as well as conductivity. Cell voltages showed an improvement of up to 190 mV for operations at 120 °C compared to earlier studies conducted at 80 °C for similar PBI-blended membranes. It was established that both chemically stable and conductive PBI-blended membranes, suitable for SO2 electrolysis above 100 °C, could be obtained by varying the composition of selected polymer components. Highlights: Partially fluorinated polymer blend components. Excellent chemical stability noted for base excess PBI-blended membranes. Improved SO2 electrolyzer performance noted at 120 °C. Preliminary voltage monitoring indicate promising long term stability at 120 °C.